(untitled) (Development Engineering Conferences Center Articles Database, 2024)
Composite materials can be used as coatings in various industries, including chemical and water industries, to prevent damage and corrosion of equipment. Nano-reinforcements, due to their very small dimensions and high surface area compared to conventional reinforcements, improve the desired properties and are a good substitute for conventional composites. Considering the mentioned factors, choosing a suitable nano-composite system for use as a resistant and strong coating in equipment is necessary, which can reduce the operating costs of companies. In this thesis, the physical, mechanical, and wear properties of vinyl ester nano-composites reinforced with graphene oxide have been investigated. First, three different samples of vinyl ester nano-composites containing 0.5%, 1.0%, and 2.0% by weight of graphene oxide/vinyl ester composites were prepared and fabricated. Then, the properties of the samples were obtained using tensile, reactivity, XRD, and SEM tests. The results showed that the optimum amount of graphene oxide nanoparticles in the weight percentage of 0.1% compared to vinyl ester resin was 151.9 degrees Celsius in the reactivity test and 87.06 megapascals in the tensile strength test.